ARE WE COMPREHENSIVELY TREATING PATIENTS FROM ASSESSMENT TO COMPLETION OF TREATMENT PLAN?- A RETROSPECTIVE ANALYSIS - Raj VPRB, Ranjith; Jayaraj, Gifrina; Thamaraiselvan, Murugan (International Journal of Psychosocial Rehabilitation, 2020)
Aim: Any treatment is designed and performed to increase the quality of life of the patient. The success of any treatment depends on how far the patient is relieved from the disease. This will ultimately lead to an improvement in the health and well-being of the patient. The formulation, execution, and completion of a treatment plan require complete determination from the patient as well as the practitioner, and this is dependent upon various factors. This study aims to comprehensively analyse the assessment of the patient until the completion of the treatment plan in a dental institution.Materials and Methods: A retrospective cross-sectional study was done by assessing 86,000 patient records who visited as an outpatient in a dental institution in south India from June 2019 to March 2020. Data of 100 random patients were obtained by random sampling to prevent bias. Fields such as unique patient ID, treatment completed, treatment under progress, total treatment planned, type of case: emergency/normal, Type of Treatment Plan: Interim/Cumulative were recorded in Microsoft Excel Software and then exported to IBM SPSS Statistics Software for further analysis where frequency, chi-square, & descriptive statistics were done.Results: Average percentage of treatment completed: 60.05% (SD 66.67), Number Of emergency cases: 33 Number of normal cases: 67, average percentage of treatment pending: 39.95% (SD = 33.33), total number of treatment planned ranged from 1-31, 100% of the treatment was completed, majorly in cases with less than 5 treatment procedures (20%). At least one planned treatment was completed for most of the patients.(88%)Conclusion: The process of diagnosis, planning, and execution of a treatment plan for each patient is unique and significant; usually in emergency cases and cases with aesthetic requirements, the patients are determined to relieve the pain & resolve their aesthetic needs and are not willing to complete the treatment plan. Hence, proper knowledge, awareness, and practice are required for both the patient as well as the practitioners.